2022
DOI: 10.1002/hcs2.17
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making for early major amputation in selected diabetic foot ulcer patients with peripheral vascular disease

Abstract: Objective: To estimate the costs from delaying major amputation in patients with concurrent diabetic foot ulcer and peripheral vascular disease. We seek to model economic benefits from saved costs from promoting timely major amputations among these patients. Methods: Retrospective modeling using data from National University Hospital, Singapore. We identified patients who might have delayed major amputations by applying a hierarchical clustering algorithm. We then modeled the transitions of all patients over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Despite the availability of several treatment options, managing DFU remains one of the most challenging complications associated with diabetes. 80,81 4 | STEM CELL THERAPY…”
Section: Gradementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of several treatment options, managing DFU remains one of the most challenging complications associated with diabetes. 80,81 4 | STEM CELL THERAPY…”
Section: Gradementioning
confidence: 99%
“…If the patient's condition deteriorates to the point that maintaining a limb is no longer an option, amputation could be a life‐saving alternative. Despite the availability of several treatment options, managing DFU remains one of the most challenging complications associated with diabetes 80,81 …”
Section: Conventional Treatment Of Dfumentioning
confidence: 99%
“…Other considerations, such as glycemic control, vascular assessment, use of sensitive antibiotics, and psychotherapy in patients with DFU, have been fully considered in previous research ( 43 , 44 ). In addition, amputation may be a life-saving option if the patient’s condition becomes too severe to salvage a limb ( 45 , 46 ). Although there are many therapeutic methods, treating DFU is still one of the thorny problems in the complications of diabetes.…”
Section: Conventional Treatment For Dfumentioning
confidence: 99%
“…Diabetic foot is one of the most severe complications of diabetes and is the leading cause of surgical non-traumatic amputation ( 3 ). Studies have found that approximately 25% of people with diabetes will suffer a DFU in their lifetime, and 30% of people with a diabetic foot will experience disease progression that would eventually leads to amputation ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%